Modified linear active disturbance rejection control for microgrid inverters: Design, analysis, and hardware implementation. (28th June 2019) - Zeng, Jiang; Huang, Zhonglong; Huang, Yiying; Qiu, Guobin; Li, Zhihua; Yang, Lin; Yu, Tao; Yang, Bo
Summary: Microgrid inverters are characterized by nonlinearities, strong coupling, and switching flexibility, by which traditional proportional‐integral control is inadequate to realize a satisfactory control performance due to its local linearization. This paper attempts to design a modified linear active disturbance rejection control (MLADRC) for voltage control of microgrid inverters. Under the framework of extended state observer, voltage error derivative is obtained indirectly by the measurement of filter capacitor current, such that the observation performance of extended state observer could be significantly improved. Furthermore, a first‐order inertial link is employed in the perturbation loop to effectively suppress observation noises. A thorough frequency response analysis of MLADRC, linear active disturbance rejection control, and proportional‐integral control is undertaken, which shows that MLADRC owns superior disturbance rejection performance than that of others. Lastly, hardware experiment validates the effectiveness and implementation feasibility of MLADRC.